Knowledge and Use Family Medicine Plants of Pasar 6th Village Kualanamu, Sumatera Utara - Safitri, Riri; Munthe, Novita Br Ginting (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Medicinal plants are very beneficial for the health of the Indonesian people. Preservation of medicinal plants can be done in the yard of the house so that it can be said as a family medicinal plant. Most people know the knowledge of the benefits of family medicinal plants from their ancestral heritage. Pasar VI Kualanamau Village is one of the villages from the Beringin District, Deli Serdang Regency, where the community still uses and grows medicinal plants in their yards. Therefore, the purpose of this study was to determine the knowledge and utilization of medicinal plants in the Pasar VI Kualanamu village community. The method used in this study is the interview method using a questionnaire. Respondents who were included in this study were people who had an interest in family medicinal plants. The results of this study indicate that the majority of the people of Pasar VI Kualanamu Village know quite a lot of types of plants that are useful as medicine, namely 44 types of plants that are known by the community that function as medicinal plants and state that all types of medicinal plants consumed by the respondents are safe for consumption. The types of medicinal plants consumed most by respondents with a percentage value of 100% include turmeric (Curcuma longa), ginger (Zingiber officinale), Red Ginger (Zingiber officinale), and lemongrass (Cymbopogon citratus). Only a few types of medicinal plants were planted (cultivated) by the respondents themselves, not all types of medicinal plants consumed by the respondents were obtained from the results of their own cultivation (cultivation), some types of medicinal plants consumed were obtained from other communities who have these types of plants.